2021
DOI: 10.1136/bmjopen-2020-046598
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of disposition decision making for patients referred for admission from the emergency department without definite medical acuity

Abstract: ObjectiveTo map the physician approach when determining disposition for a patient who presents without the level of definite medical acuity that would generally warrant hospitalisation.Data sources/study settingSince 2018, our US academic county hospital/trauma centre has maintained a database in which hospitalists (‘triage physicians’) document the rationale and outcomes of requests for admission to the acute care medical ward during each shift.Study designNarrative text from the database was analysed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A major factor may be clinicians’ perceived risks of discharging an unhoused person back to the street. Qualitative studies have shown that ED clinicians consider safety concerns when deciding to admit PEH with low medical acuity . The persistence of increased odds of admission among PEH compared with low-income housed patients suggests that the observed associations are due to unstable housing independently of other health-related social needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major factor may be clinicians’ perceived risks of discharging an unhoused person back to the street. Qualitative studies have shown that ED clinicians consider safety concerns when deciding to admit PEH with low medical acuity . The persistence of increased odds of admission among PEH compared with low-income housed patients suggests that the observed associations are due to unstable housing independently of other health-related social needs.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies have shown that ED clinicians consider safety concerns when deciding to admit PEH with low medical acuity. 43 The persistence of increased odds of admission among PEH compared with low-income housed patients suggests that the observed associations are due to unstable housing independently of other health-related social needs. For many PEH, discharge home would mean returning to the place where they were injured, potentially putting them at risk for reinjury.…”
Section: Jama Network Open | Emergency Medicinementioning
confidence: 98%
“…For example, previous work on ED patients of all ages pointed to factors, such as frailty, homelessness, unemployment, and educational level, likely to play a role in the decision to admit. 26,27 In a small qualitative study, Pope et al 28 highlighted that levels of social support and community follow-up were believed to be important factors in admission. Greysen et al 8 showed that increasing difficulty with ADLs was associated with readmission.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to admit a patient to the hospital is a complicated, multifaceted phenomenon informed by contextual details related to the patient, physician, healthcare system, and overall social support availability [8][9][10][11]. In one study, nearly half of admissions from an emergency department were "strongly or moderately" influenced by one or more non-medical factors [12].…”
Section: Introductionmentioning
confidence: 99%